Neighbourhood quality in developed and developing countries / Norainah Abdul Rahman, Dasimah Omar and Abdul Ghani Salleh - Abdul Rahman, Norainah; Omar, Dasimah; Salleh, Abdul Ghani (2012)
8eighbourhood quality is important for the residents' need and satisfaction in their housing and neighbourhood area. Most research in developed and developing countries generally used physical, social and economic factor in conceptualising the research. In developed and developing countries the neighbourhood quality uses satisfaction concept in illuminating the context of the physical factor, physical and social factor or physical, social and economic factor. The residents will evaluate the physical, social and economic factor by using the satisfaction scale with multivariable attributes. Despite increase in the use of physical, social and the economic factors among developed and developing countries, evidence from literature claimed that in Malaysia, most research used physical or physical and social factors to conceptualise the research. In this paper, extensive review on previous research in developed and developing neighbourhood quality has been conducted to gauge residents' needs in their housing and neighbourhood area. The primary objective of this paper therefore is to examine the existing variable used in neighbourhood quality in developed and developing countries. It was found that most research used multivariable in physical, social and economic factors as their conceptual framework. This paper contributes in the aspect of neighbourhood quality and had implications towards local authority policy and planning guidelines.